A imagem da esquerda no discurso da imprensa pernambucana. - Morais, Luciano José de Farias (2009)
This work aims to analyze the discourses of the press intentona Communist Pernambuco in 1935. Because these speeches helped and contributed to a negative image of the left in Brazil. Thus, several issues were relevant to an analysis of this intense study, as ideology, left and right and also as the press was used to build these issues in a distorted analysis of those who participated in the communist movement. We see listed in the official newspaper of Pernambuco left pejorative terms such as extremists, anarchy, disorder and other leading newspapers of the party (player) to see the movement as something detrimental to society. These terms have influenced the popular imagination a malicious look on the left.